Comparative analysis of liver cancer burden trends in China and worldwide between 1990 and 2021 - Chunrong Chen; Qianjie Xu; Tao Wang; Yuliang Yuan; Zuhai Hu; Xiaosheng Li; Xiaodong Zheng; Haike Lei (Frontiers in Public Health)
BackgroundThe Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2021 provides comprehensive data on liver cancer burden worldwide. This study aims to analyze and compare the trends in liver cancer burden in China and globally between 1990 and 2021.MethodsData were extracted from the GBD 2021 database, which includes incidence, prevalence, mortality, and disability-adjusted life years (DALYs) for liver cancer in 204 countries and territories. Age-standardized rates (ASIR, ASPR, ASMR, ASDR) and crude rates (CIR, CPR, CMR, CDR) were calculated. Joinpoint regression analysis was used to determine the average annual percentage change (AAPC) in liver cancer burden trends.ResultsIn China, the number of liver cancer cases increased from 96,434 in 1990 to 196,637 in 2021, while the age-standardized incidence rate (ASIR) decreased. Globally, cases increased from 244,689 to 529,202, with a slight increase in ASIR. The age-standardized prevalence rate (ASPR) in China remained stable, while globally it increased. Age-standardized mortality rates (ASMR) and age-standardized DALY rates (ASDR) decreased in both China and globally. Males had higher rates than females in all age groups. The peak age for liver cancer burden occurred earlier in Chinese males compared to the global average.ConclusionThe liver cancer burden in China has declined over the past three decades, with a more significant decrease in China than globally. However, China still faces a higher burden compared to the global average. The earlier peak in liver cancer burden among Chinese males suggests the need for targeted prevention and control measures, especially in light of the impact of risk factors like hepatitis B and C, alcohol consumption, drug abuse, obesity, diabetes and tobacco use. Globally, liver cancer remains a significant public health challenge with rising incidence and prevalence rates, emphasizing the need for a comprehensive global approach to liver cancer prevention.